Cancer biomarkers and mass spectrometry-based analyses of phospholipids in body fluids. (February 2013) - Jelonek, Karol; Ros, Malgorzata; Pietrowska, Monika; Widlak, Piotr
The lipid profiles of body fluids reflect the general condition of the whole organism and can indicate the existence of certain diseases such as cancer. Qualitative and quantitative assessment of lipids in blood and other body fluids could reveal novel biomarkers for early detection and prognosis of cancer; in addition, it may be useful in monitoring the efficacy and toxicity of anticancer treatment. Consequently, lipidomics is an emerging approach in cancer research. Phospholipids make up an important lipid class, which is particularly suitable for analyses by mass spectrometry. Mass spectrometry methods involving 'soft' ionization techniques, such as electrospray ionization and matrix-assisted laser desorption ionization, which are well established in the proteomics field, have also been implemented in analyses of lipids. This review focuses on the application of electrospray ionization and matrix-assisted laser desorption ionization mass spectrometry in the characterization of structure and composition of phospholipids present in biofluids, and their importance for cancer-related problems.